Radiographic progression by Prostate Cancer Working Group (PCWG)‐2 criteria as an intermediate endpoint for drug development in metastatic castration‐resistant prostate cancer. (17th July 2014) - Sonpavde, Guru; Pond, Gregory R.; Armstrong, Andrew J.; Galsky, Matthew D.; Leopold, Lance; Wood, Brian A.; Wang, Shaw‐Ling; Paolini, Jolanda; Chen, Isan; Chow‐Maneval, Edna; Mooney, David J.; Lechuga, Mariajose; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate the association of radiographic progression defined by Prostate Cancer Working Group (PCWG)‐2 guidelines and overall survival (OS) in men with metastatic castration‐resistant prostate cancer (mCRPC). Patients and Methods Two trials that used PCWG‐2 guidelines to define progression were analysed: a randomized phase II trial (n = 221) comparing first‐line docetaxel‐prednisone plus AT‐101 or placebo, and a phase III trial (n = 873) comparing prednisone plus sunitinib or placebo after docetaxel‐based chemotherapy. Cox proportional hazards regression models were used to estimate the association of radiographic progression with OS. Landmark analyses compared progressing patients with those who had not progressed. Sub‐analyses compared patients removed from trial for progression vs other reasons. Results An increased risk of death was seen for radiographic progression at landmark times from 6 to 12 months with docetaxel‐based therapy (hazard ratio [HR] >1.7 at all time‐points). An increased risk of death was also seen with post‐docetaxel prednisone alone or with sunitinib for progression at landmark times from 2 to 8 months (HR >2.7 at all time‐points). Kendall's τ was 0.50 (P < 0.001) in the setting of docetaxel‐based therapy and 0.34 (P < 0.001) in the post‐docetaxel setting for association between radiographic progression and death amongst patients with both events. Removal from study due to radiographic progression was associated with a significantly lower OS compared with removal for other reasons in both trials. Limitations of a retrospective analysis apply and there was no central radiology review. Conclusions Radiographic progression by PCWG‐2 criteria was significantly associated with OS in patients with mCRPC receiving first‐line docetaxel‐based chemotherapy or post‐docetaxel therapy. With external validation as a surrogate endpoint in trials showing survival benefits, the use of radiographic progression‐free survival may expedite drug development in mCRPC, which has been hampered by the lack of intermediate endpoints.